A study of selected principles of international environmental law in the light of 'sustainable development' - Fellrath, Isabelle (1998)
Since the late 1980s, the terms of 'sustainable development' have been frequently referred to both in international environmental law instruments and in the doctrine. In spite of such references, however, sustainable development has remained poorly developed in terms of its meaning and of its practical and normative implications. This thesis purports to come out with a partial picture of what sustainable development means (or does not mean) in the restricted context of international environmental law. To do so, it will try to identify in which respect and how far sustainable development has influenced and has been reflected in the evolution of some selected principles of that law. Each principles is considered in an evolutionary perspective, from the time of its inception to the time of its 'association' to sustainable development.